Co-designing for desistance: Developing My Journey to support people in the criminal justice system - Morgan, Gemma (European journal of probation, 2025)
This article explores the development of My Journey, a web-based application (app) co-designed with people in the criminal justice system (CJS) to facilitate desistance. Developed in partnership with Include UK, a third-sector organisation, the app aims to promote agency, improve access to resources, and facilitate practitioner support for people in the CJS. Grounded in desistance theories, My Journey embodies principles such as agency, strengths-based approaches, and positive relationship-building, promoting person-centred and individualised support. The co-design process engaged five practitioners and 41 people with lived experience, ensuring the app reflected their needs. By integrating theoretical insights with practical application, My Journey represents an innovative attempt to translate desistance theories into a useable digital technology to support people and practitioners in the CJS. This article outlines the key themes of desistance translated into the app, details the co-design methodology, and presents the app’s features, highlighting its potential to bridge theory and practice.